2007
DOI: 10.1212/01.wnl.0000260970.63493.c8
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic transverse myelitis

Abstract: Transverse myelitis is a focal disorder of the spinal cord in which an immune-mediated process results in neural injury. In this large retrospective study, we compare patients who received one of four treatments to identify the most effective therapies. We identified subsets of patients who received clinical benefit from plasma exchange or cyclophosphamide being included in their treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 5 publications
1
67
1
4
Order By: Relevance
“…Data suggest that certain conditions have preferential responses to certain therapeutic interventions. 41 For example, SLE patients with ATM may respond to cyclophosphamide whereas patients with NMO benefit from plasmapheresis (PLEX). In patients without a prior history suggestive of a systemic condition, the treatment of TM has to be approached empirically.…”
Section: Outcomes Prognosis and Measurementmentioning
confidence: 99%
“…Data suggest that certain conditions have preferential responses to certain therapeutic interventions. 41 For example, SLE patients with ATM may respond to cyclophosphamide whereas patients with NMO benefit from plasmapheresis (PLEX). In patients without a prior history suggestive of a systemic condition, the treatment of TM has to be approached empirically.…”
Section: Outcomes Prognosis and Measurementmentioning
confidence: 99%
“…Several small studies in pediatric patients found improved outcomes with IV methylprednisolone (Sebire et al, 1997a;Lahat et al, 1998;Defresne et al, 2001a). A more recent study looking at ATM treatment in adults also found IV methylprednisolone beneficial, but not in patients affected by complete loss of motor and sensory function (Greenberg et al, 2007). In this study, 122 patients who presented with ATM were analyzed retrospectively for response to treatment.…”
Section: Treatmentmentioning
confidence: 94%
“…In addition to PLEX and IVIg, uncontrolled case series suggest that use of immune suppressants including CTX (idiopathic transverse myelitis, SLE) (D'Cruz et al, 2004;Greenberg et al, 2007), rituximab (NMO) Jacob et al, 2008a), and azathioprine (NMO), (Bichuetti et al, 2010) might be helpful.…”
Section: Treatmentmentioning
confidence: 99%
“…Several alternatives, including plasmapheresis [48][49][50][51], cyclophosphamide [48,52,53], intravenous immunoglobulin G (IV-IG) [54][55][56][57][58], and natalizumab [59] have been studied with plasmapheresis as the only option supported by strong clinical evidence. The recent American Academy of Neurology guideline published in January 2011 [60] recommends considering using plasma exchange as a secondary treatment for severe flares in remitting-relapsing MS.…”
Section: Second Line Of Treatment For Ms Relapse Cases Unresponsive Tmentioning
confidence: 99%